2011
DOI: 10.1016/j.ejcts.2010.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long intensive care unit stay following cardiac surgery in children

Abstract: Some patients with a risk of prolonged hospitalization may be identified preoperatively, the others just after the operation. Optimizing preoperative status and aggressive treatment of complications may have significant influence on the duration of hospitalization in intensive care units. The knowledge of risk factors may facilitate organizational procedures and rational bed management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 23 publications
9
46
0
3
Order By: Relevance
“…As surgical techniques and perioperative management of neonates undergoing surgery for congenital heart disease continue to evolve, mechanical ventilation continues to be a necessary and important component of postoperative management [1,2]. In a small but substantial number of neonates, initial attempts at extubation and liberation from mechanical ventilation fail and reintubation is required.…”
Section: Introductionmentioning
confidence: 99%
“…As surgical techniques and perioperative management of neonates undergoing surgery for congenital heart disease continue to evolve, mechanical ventilation continues to be a necessary and important component of postoperative management [1,2]. In a small but substantial number of neonates, initial attempts at extubation and liberation from mechanical ventilation fail and reintubation is required.…”
Section: Introductionmentioning
confidence: 99%
“…in the operating suite or shortly after arrival to the intensive care unit) relatively common in pediatric cardiac surgery [1][2][3]. Many children however, particularly neonates, continue to require mechanical ventilator support for several days or even weeks postoperatively [4][5]. The determination of readiness for extubation from mechanical ventilation in critically-ill infants and children in general continues to be challenging for pediatric intensive care providers [6].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, patients who suffered any form of pulmonary complications had longer duration of mechanical ventilation (p <0.01), longer post operative ICU stay (p <0.01) and longer post operative hospital stay (p <0.01). Studies also showed that pulmonary complications are a frequent cause for delayed recovery following cardiac surgery and including prolonged duration of mechanical ventilation specially in young children and prolonged ICU stay 9,31 .…”
Section: Discussionmentioning
confidence: 99%